Laser-interference pulse number dependence of surface chemistry and sub-surface microstructure of AA2024-T3 alloy - Sabau, Adrian S.; Meyer, Harry M.; Leonard, Donovan N. (Optics and laser technology, 2020)
•Surface chemistry of aluminum alloy after two-beam laser interference processing.•Dissolution of CuMn-rich precipitates over 500–800 nm depth due to laser processing.•Sharp features from rolled sheet surface were smoothed by laser-structuring.•Al oxide layer is modified compared to that of the baseline specimen.•Most of surface organic and inorganic contaminants were removed, cleaning the surface. The laser-based treatment of a metal surface is an intrinsically non-chemical technique that can alter both the topology and chemistry of surfaces.  A laser-based treatment for coating and joining applications can offer alternative surface preparations to the chemically-based surface preparation techniques, which are subject to severe environmental protection and hazardous-waste management considerations. In this study, the surface chemistry and sub-surface microstructural changes are investigated for a novel surface processing method using laser interferometry produced by two beams of a pulsed Nd:YAG laser. The two-beam laser-interference allowed the structuring of the surface at length scales much less than that of the laser beam spot. Surface chemistry changes in the oxide layer of AA 2024-T3 aluminum alloy rolled sheet due to laser processing were investigated using x-ray photoelectron spectroscopy (XPS). Near surface microstructural changes have been investigated with scanning electron microscopy and energy dispersive x-ray spectroscopy (SEM/EDS), and scanning transmission electron microscopy (STEM) as a function of number of interfering laser shots. SEM microstructure pictures of the top surface shows the minimization of surface defects, as all of the sharp features from a rolled sheet surface were smoothed by laser-structuring. STEM images indicate that the laser-interference processing reduced the formation of CuMn-rich precipitates over a 500–800 nm depth from the top surface. XPS data indicated that the Al oxide layer is modified compared to that of the baseline specimen and that the oxide thickness increases with the number of shots per spot. The additional thicker oxide on Al alloys is expected to increase the corrosion resistance of the coated Al 2024.